A reappraisal of atypical absence seizures in children and adults: therapeutic implications. (22nd November 2019) - Brigo, Francesco; Striano, Pasquale; Belcastro, Vicenzo
ABSTRACT: Introduction : Atypical absences are generalized epileptic seizures typically affecting children with severe epilepsies and learning difficulties along with other seizure types. Video-EEG is essential for their diagnosis. Recently, atypical absence seizures have been reported as a hallmark of some developmental and epileptic encephalopathies. Areas covered : This is a narrative review of the literature which describes the electroclinical features of atypical seizures, the characteristics of developmental epileptic encephalopathies in which this seizure type can occur, and the evidence supporting the use of individual antiseizure drugs for the treatment of atypical absences. Expert opinion : Treatment of absence seizures typically relies on ethosuximide (ineffective against tonic-clonic seizures), valproate (associated with larger proportion of adverse events), or lamotrigine (less effective than the other two). However, unlike typical absences, atypical absences are usually intractable, persist lifetime, and their prognosis depends on the underlying etiology or associated epilepsy syndrome. Besides efficacy, other relevant factors, such as drug formulation, ease of titration and dosing, and drug interactions, should be considered. Drugs that may worsen epilepsy, cognition and behavior should be avoided. In the vast majority of patients, a polytherapy is required, although usually with limited efficacy. Finally, epilepsy syndromes featuring atypical absences require a multidisciplinary approach.